The Influence of Product Quality and Promotion on Consumer Satisfaction - Hadi, Abdul; Suryani, Eva; Bismark, Irma Auliyah (CV. Strata Persada Academia, 2024)
This study comprises two independent variables, Product Quality (X1) and Promotion (X2), and one dependent variable, Consumer Satisfaction (Y). This research is both descriptive and causal. The population comprises consumers utilizing wedding services in Bum-Nag Iliran Batang Suliti Nagari Pakan Rabaa, Koto Parik Gadang Diateh District, South Solok Regency—accidental sampling, which included a cohort of 30 individuals. Validity and reliability assessments were conducted to acquire valid and dependable instruments. The study's findings indicated that at Bum-Nag Iliran Batang Suliti Nagari Pakan Rabaa Utara, Koto Parik Gadang Diateh District, South Solok Regency: Product quality is rated as satisfactory, with an average score of 3.54 and a response achievement level of 71.0%. The promotion is rated positively, with an average score of 3.52 and a respondent achievement rate of 70.0%. Consumer satisfaction ranks as a commendable criterion, with an average score of 3.54 and a respondent achievement rate of 70.9%. Product Quality does not significantly influence Consumer Satisfaction, as indicated by a significance level of 0.894, which exceeds 0.05. The calculated t value of 0.134 is less than the critical t value of 1.7033 from the t table, leading to the acceptance of H01 and the rejection of Ha1. Promotion significantly influences Consumer Satisfaction, with a significance level of 0.000 < 0.05. The calculated t value is 4.424, exceeding the t table value of 1.7033, leading to the rejection of H02 and acceptance of Ha2. The F test results indicate a calculated F value of 21.324, exceeding the F table value of 3.354, with a significance value of 0.000, below the alpha level of 0.05. Consequently, H03 is rejected, and Ha3 is accepted, signifying that Product Quality and Promotion significantly affect Consumer Satisfaction.